Probiotics supplementation in children with asthma: A systematic review and meta‐analysis. (27th July 2018) - Lin, Jilei; Zhang, Yin; He, Chunyan; Dai, Jihong
Abstract : Aim: To systematically review the effects of probiotics supplementation in children with asthma. Methods: An electronic search was conducted on PubMed, Embase, Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure Database, CQ VIP Database and Wanfang Data until November 2017. The reference lists of included studies and pertinent reviews were checked for supplementing our search. Randomised control trials that compared probiotics versus placebo were included. Results: Eleven studies with a total of 910 children met eligibility criteria. The pooled data revealed that the proportion of children with fewer episodes of asthma was significantly higher in the probiotics group than in the control group (risk ratio 1.3, 95% confidence interval (CI) 1.06–1.59); the reduction of IL‐4 (mean differences −2.34, 95% CI −3.38, −1.29) and the increasing of interferon‐γ (mean differences 2.5, 95% CI 1.23–3.76) was also significant after the treatment of probiotics. Nevertheless, no statistical significance was observed in childhood asthma control test, asthmatic symptom in the day and night, the number of symptom‐free days, forced expiratory volume in the first second predicted and peak expiratory flow. Conclusions: This systematic review does not confirm or rule out the beneficial effects of probiotics supplementation in children with asthma. More well‐designed randomised control trials with larger sample sizes need to be conducted to evaluate the effects of probiotics in children with asthma in the future.